A HUMAN IN SPACE OF MATERIAL CULTURE - Nadezhda V. Mihailova (Russian Studies in Culture and Society)
Purpose. The article is devoted to analysis of material culture as space of human existence. The subject of the analysis is a system of human relations with space of material culture. The author aims to reveal essence of a man as a biosocial being through analysis of a structure of material culture and its place in a cultural system as a whole.